PENGARUH KOMUNIKASI TERHADAP IMPLEMENTASI PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI DESA WISATA DANAU TADOW DI KELURAHAN SEDAU KOTA SINGKAWANG - Sri Agus Nayang Sari E.42009086 (FISIP Universitas Tanjungpura Pontianak, 2022)
This essay aimed to gain an understanding and explanation of the Influence of Communication on the Implementation of the National Program for Community Empowerment (PNPM) self-Tourism Village in the Village of Lake Tadow Sedau Singkawang. The title of this essay is based on issues raised with regard to the implementation of PNPM Mandiri in the tourist village of Lake Village Tadow Sedau Singkawang in which implementation of the program has not been fully effective. This study uses quantitative methods with 57 respondent. The result of this research indicate that there is significant relationship between communication with the implementation of the National Program for Community Empowerment (PNPM) independent village in the Village of Lake Tadow Sedau Singkawang. Correlation coefficient of these two variables is equal to 0.562. Based on the value of coefficient determination shows that the Influence of Communication on the Implementation of PNPM self-Tourism Village in the Village of Lake Tadow Sedau Singkawang is 31.58%, while the remaining 68,42% is the other factors that not examined in this study. Keywords : Communication, Implementation, National Community Empowerment Program.